Closed system RT-qPCR as a potential companion diagnostic test for immunotherapy outcome in metastatic melanoma. Issue 1 (18th September 2019) - Gupta, Swati; McCann, Leena; Chan, Yvonne G. Y.; Lai, Edwin W.; Wei, Wei; Wong, Pok Fai; Smithy, James W.; Weidler, Jodi; Rhees, Brian; Bates, Michael; Kluger, Harriet M.; Rimm, David L.
Abstract : Background: In melanoma, there is no companion diagnostic test to predict response to programmed cell death 1 (PD-1) axis immune checkpoint inhibitor (ICI) therapy. In the adjuvant setting, only one in five patients may benefit from ICI, so a biomarker is needed to select those that may or may not benefit. Here, we test a new 4-gene multiplex immunotherapy panel with research use only (RUO) prototype mRNA expression profile on the GeneXpert closed system using real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR) for association with clinical benefit after treatment with ICI therapy in metastatic melanoma patients. Methods: Pretreatment formalin-fixed paraffin-embedded (FFPE) tissue sections from melanoma patients treated with anti-PD-1 therapy (pembrolizumab, nivolumab, or ipilimumab plus nivolumab) between 2011 and 17 were selected from the Yale Pathology archives. FFPE sections were macrodissected to enrich for tumor for quantitative assessment of CD274 (PD-L1), PDCD1LG2 (PD-L2), CD8A, and IRF1 by RT-qPCR multiplex mRNA panel. Multiplex panel transcript levels were correlated with clinical benefit (complete response [CR], partial response [PR], stable disease [SD]); disease outcomes (progression-free survival [PFS] and overall survival [OS]); and protein levels assessed by quantitative immunofluorescence (QIF). Results: Transcript levels were significantly higher in responders (CR/PR/SD) than in nonresponders (PD) for CD8A ( p  = 0.0001) and IRF1 ( p  = 0.0019). PFS was strongly associated with high CD274 ( p  = 0.0046), PDCD1LG2 ( p  = 0.0039), CD8A ( p  = 0.0002), and IRF1 ( p  = 0.0030) mRNA expression. Similar associations were observed for OS with high CD274 ( p  = 0.0004), CD8A ( p  = 0.0030), and IRF1 ( p  = 0.0096) mRNA expression. Multivariate analyses revealed significant PFS and OS associations with immunotherapy panel markers independent of baseline variables. Exploratory analyses revealed a novel significant association of high combined CD274 & PDCD1LG2 (L1/L2 ) transcript expression with PFS ( p  < 0.0001) and OS ( p  = 0.0011), which remained significant at a multivariate level for both PFS (HR = 0.31) and OS (HR = 0.39). Conclusions: Individual immunotherapy panel markers CD274, PDCD1LG2, CD8A, IRF1 and a combined L1/L2 mRNA levels show promising associations with melanoma immunotherapy outcome. The turnaround time of the test (2 h) and easy standardization of the platform makes this an attractive approach for further study in the search for predictive biomarkers for ICI.